2018
DOI: 10.1111/rda.13133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of astaxanthin on the quality of boar sperm stored at 17°C, incubated at 37°C or under in vitro conditions

Abstract: The aim of the study was to investigate the effect of the antioxidant astaxanthin on boar semen. Twenty ejaculates from 10 boars (two ejaculates/boar) were extended and split in three groups: semen control (SC), solvent control (C; semen with dimethyl sulfoxide, the diluent of astaxanthin) and semen with astaxanthin (A) in concentration 0.5 μmol/L. Sperm quality parameters (motility and kinetics, morphology, viability, functional integrity of sperm plasma membrane by Hypo-Osmotic Swelling Test [HOST] and DNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The reported effects of AXN supplementation on sperm acrosomal integrity are variable. In boar (Basioura et al, 2018) and ram (Fang et al, 2015), AXN supplementation resulted in a milder or no significant increase in acrosomal integrity after cooled storage at 4°C, while dietary supplementation of AXN in men with infertility issues resulted in significant improvement of acrosomal integrity (Comhaire et al, 2005). However, another report showed that in low ROS conditions similar to capacitation, there was a reduction in acrosomal integrity (Dona et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The reported effects of AXN supplementation on sperm acrosomal integrity are variable. In boar (Basioura et al, 2018) and ram (Fang et al, 2015), AXN supplementation resulted in a milder or no significant increase in acrosomal integrity after cooled storage at 4°C, while dietary supplementation of AXN in men with infertility issues resulted in significant improvement of acrosomal integrity (Comhaire et al, 2005). However, another report showed that in low ROS conditions similar to capacitation, there was a reduction in acrosomal integrity (Dona et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in rats, an AXN-supplemented diet significantly reduced the ROS level and increased sperm fertility through enhanced sperm viability, linearity and plasma membrane integrity (Comhaire et al, 2005;Mortazavi, Salehi, Alizadeh, Vahabian, & Roushandeh, 2014). AXN has been reported to effectively preserve the quality of cooled boar (Basioura, Boscos, Parrilla, Tsousis, & Tsakmakidis, 2018) and ram semen (Fang et al, 2015). Moreover, ANX enhanced the post-thaw sperm quality of boar (Lee & Kim, 2018) and bulls (Farzan, Chamani, & Varnaseri, 2014).…”
mentioning
confidence: 99%
“…The ability of antioxidant agents to control the harmful effects of reactive oxygen species on spermatozoa has been extensively investigated, to further their use as the main regulators of these oxidant molecules. However, the main focus of the present study was on sperm quality rather than the influence of antioxidant agents on metabolic functionality and sperm physiology [4043]. Here, for the first time we evaluated the antioxidant and metabolic effects of murtilla as an antioxidant supplement in boar MR-A semen extender in an attempt to improve sperm refrigeration based on the behaviour of sperm metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Basioura et al demonstrated the beneficial and protective effect of astaxanthin on boar semen quality under 17°C storage, 37°C and 38.5°Cin vitro incubation. 24 The nuclear transcription factor Nrf2 is one of the important antioxidant regulators involved in the maintenance of the redox state for the defense of intracellular oxidative stress. 25,26 Heme oxygenase 1, a phase II detoxifying enzyme regulated by Nrf2, has been reported to be a critical beneficial regulator in oxidative stress-induced diseases.…”
Section: Discussionmentioning
confidence: 99%